Coeficiente de cultivo e lâminas de irrigação do maracujazeiro amarelo nas condições semiáridas - Nogueira, Eliomar (2011)
This work aims to determine the crop coefficie nt of the yellow passion fruit and to find irrigation levels that can raise the yield a nd quality of passion fruit production under the environmental conditions of the semiarid re gion of Piaui (Br). The experiment was conducted at the Projeto Piloto de Fruticultura Irrigada (Irrigated Fruit Culture Pilot Project) of the CODEVASF, in Santa Rosa, PI (06 ° 47 '5 6''S, 42 ° 17' 17''W). We used randomized blocks with six treatments and four replications, with four plants to a plot. The treatments (irrigation levels) were defined as percentages of the reference evapotranspiration (ETo): T1 (25% ETo), T2 (50% ETo), T3 (75% ETo), T4 ( 1 00% ETo), T5 (125% ETo) and T6 (150% ETo). It was installed a battery with three tensiom eters per treatment at depths of 0.10 m, 0.30 m and 0.50 m, to monitor the soil water. Determining the crop coefficient (Kc), we used the soil water balance, and for obtaining that, two batteries were installed, with tensiometers placed at depths of 0.10 m, 0.30 m 0.50 m within a radius of 0.30 m and 0.60 m from the stems of the plants in T4. The Kc values were estimated in the 41-240 days a fter transplanting (DAT). The irrigation le vels of 408.25 mm (T1), 463.41 mm (T2) 535.11 mm (T3), 609.98 mm (T4), 704.71 mm (T5) and 826.02 mm (T6) were applied on performing the experiment. We evaluated the morphological and physiologic al growth variables of yellow passion fruit (plant height, stem diameter, number of internod es, leaf area, leaf number and leaf water potential) and production traits (yield, fruit numb er, fruit weight, fruit transverse diameter and fruit longitudinal diameter). Analysis of varia nce showed that the irrigation significantly influenced stem diameter (P <0.05) in assessments conducted in December 2009, January and February 2010; leaf area (P < 0.01) for assessments conducted from Januar y to April 2010; number of leaves (P <0.05) for assessments conducted in March 2010 and (P <0.01) in April 2010; leaf water potential (P <0.01) at all testing times. Besides, the number of fruits (P<0.05), the average fruit weight (P <0.05) and the productivity (P <0.05) were found significantly responding to the irrigation level. Maximum yield (6763 kg ha-1) was obtained in 60 days of harvest, ie 25% of potential annual production of passion fruit was obtained with an irrigation level of 763.80 mm...Estimating to its full potential to the first year of production we obtained a value of 27,052 kg ha-1 yr -1. As for the average fruit weight, it ranged from 0.207 kg (T6) to 0,159 kg (T1). The maximum number of fruits (33 119 fruit ha -1) was obtained with an irrigation level of 760.21 mm. The Kc values ranged from 0.43 to 1.04 with a maximum recorded value at 211 to 220 DAT. The average Kc obtained at the vegetative stage, was 0.57, and the average Kc at the production stage(flower ing and fruiting)was 0.94. Therefore: The irrigation level most suitable for the passion fruit must be between 72% and 100% ETo; The assessed morphophysiological growth variables of the yellow passion fruit are influenced by the variation of irrigation level applied to culture; The yield, average weight and fruit number of the yellow pa ssion plant are also influenced by the same variation of irrigation level